A simple and reliable proposal to determine the technical feasibility of biogas use and the energetic self-sustainability in UASB-based sewage treatment plants - Tayane Cristiele Rodrigues Mesquita (IWA Publishing, 2021)
The biogas produced in UASB-based sewage treatment plants (STPs) is rarely used for energy purposes and its potential is often unknown. This study aimed to propose a simple and reliable method based on energy balance to determine the technical feasibility of biogas use and the energy self-sufficiency of UASB reactors. To this end, we considered (i) electric power production (E) and (ii) electric power consumption (Econ) ascribed to sewage pumping stations (SPSs) at different pressure heads (0 to 4 m, 4.1 to 8 m, 8.1 to 12 m, and 12.1 to 16 m). The technical feasibility of biogas use was assessed by evaluating if the flow of biogas produced in the STPs would be sufficient for the functioning of a commercial motor-generator. The linear model fit to estimate the biogas energy potential (y-axis) in STPs and the sewage flow (x-axis) is represented by y = 122.65x (R2 = 0.64). In total, 1,054 STPs in Brazil use UASB reactors as treatment units, of which nearly 31% are located in the southeast. However, only 11.2% of these STPs, which serve populations of over 29,981, presented technical feasibility to recover biogas. The mathematical equations proposed in this study to estimate the net electric power production in UASB-based STPs are relevant tools for sanitation companies and can enable studies to be performed for the implementation of energy self-sufficiency projects in Brazil. HIGHLIGHTS Only 11.2% of UASB-based STPs in Brazil present technical feasibility for biogas production.; Among the assessed STPs, only those serving populations over 29,981 presented technical feasibility for biogas use.; The energy self-sufficiency of UASB reactors can be determined from mathematical equations using simple input data.;